2015
DOI: 10.4236/ajac.2015.65045
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ppt Level Chromium(VI) Using the Gold Nano-Flakes Electrodeposited on Platinum Rotating Disk Electrode and Modified with 4-Thiopyridinium

Abstract: The nano-gold layer formed on the platinum rotating disk electrode (nano-Au/Pt-RD) inherited the catalytic property for Cr(VI) reduction from platinum surface and owned the good features of nano-gold such as insensitivity with hydrogen ion, high surface area, augmenting diffusion of Cr(VI) and ability for self-assembling with 4-pyridine-ethanethiol (PET) through Au←S linkages, to form PET/nano-Au/Pt-RD electrode capable of accumulating Cr(VI) from sample. The obtained PET/ nano-Au/Pt-RD electrode showed an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…In our previous study [11], the electro-deposition of gold nano-flakes (nano-Au) on electrode surface of RD electrode from HAuCl 4 solution depends on the activity of electrode surface for the reduction of HAuCl 4 into nano-Au, the transferring rate of HAuCl 4 to electrode surface and the deposition time (t P ). The activity of electrode surface is conducted by the deposition potential (E P ).…”
Section: The Optimization Of Electro-depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study [11], the electro-deposition of gold nano-flakes (nano-Au) on electrode surface of RD electrode from HAuCl 4 solution depends on the activity of electrode surface for the reduction of HAuCl 4 into nano-Au, the transferring rate of HAuCl 4 to electrode surface and the deposition time (t P ). The activity of electrode surface is conducted by the deposition potential (E P ).…”
Section: The Optimization Of Electro-depositionmentioning
confidence: 99%
“…Following the procedures from previous studies [9][10][11][12][13], the Au-RD working electrode was polished with the water slurry of 0.05 lm alumina particles. The residual polishing material was removed using ethanol and then water in an ultrasonic bath.…”
Section: Preparation Of Nano-au/au-rd Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…The prepared sensor was utilized for the determination of Cr(VI) in contaminated groundwater with an average recovery of 96%. Moreover, Huy Du Nguyen et al [ 52 ] reported a new voltametric sensor built on the modification of a platinum rotating disk electrode by gold nano-flakes and 4-pyridine-ethanethiol through electrodeposition approach. The developed sensor showed excellent properties for Cr(VI) sensing in Coastal water with enhanced sensitivity and reproducibility and a very low detection limit (0.001 µg·L −1 ).…”
Section: Electrochemical Sensors For Hexavalent Chromium Determinamentioning
confidence: 99%
“…Exposure to Cr can produce different point mutations in DNA, chromosomal damage, and oxidative alterations in proteins in addition to adduct formation. Because each form of Cr has a different level of toxicity, the health impacts of each are varied [1][2][3].…”
Section: ■ Introductionmentioning
confidence: 99%